DOI: 10.18297/etd/1372
|View full text |Cite
|
Sign up to set email alerts
|

Fighting for success : the use of resources by NGOs in the anti-human trafficking social movement.

Abstract: This thesis is an archival document analysis that will illustrate the importance of effective use of resources on the overall success of an anti-human trafficking organization. While there are multiple studies on resource mobilization and movements in general, little work has emerged regarding successful mobilization strategies in the anti-human trafficking movement. With my research, I pay particular attention to two groups and consider how their interactions with various resources influence their success.Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In line with this, Oberschall (2017) found that NGOs do not need to struggle to mobilize resources when it gains legitimacy. For instance, government recognition is one of the major indicators for the success of a movement (Stapleton, 2013). Collectively, influenced by NGOs, the effects of political opportunities can be enhanced when it is accepted by institutions (e.g.…”
Section: Institutional Opportunities and Non-governmental Organizatio...mentioning
confidence: 99%
“…In line with this, Oberschall (2017) found that NGOs do not need to struggle to mobilize resources when it gains legitimacy. For instance, government recognition is one of the major indicators for the success of a movement (Stapleton, 2013). Collectively, influenced by NGOs, the effects of political opportunities can be enhanced when it is accepted by institutions (e.g.…”
Section: Institutional Opportunities and Non-governmental Organizatio...mentioning
confidence: 99%